Between the turbulent waters of the political world and the placid waters of the apolitical sound: James Comey’s book review. Comey J. A Higher Loyalty: Truth, Lies, and Leadership. Memoirs of the FBI Director / translated into Ukraine by Nazar Starovoit. Kyiv.: Laboratory, 2022. 288 p. - Viktor Lushchak (Американська історія і політика, 2023)
This review is an analysis of an autobiography book by the professional prosecutor and former director of the FBI James Comey. Comey's memoirs were released in the U.S. in 2018 when Robert Muller's investigations about Russian interference in the U.S. election had gained momentum. The Ukrainian translation was published in 2022 (Kyiv, Ukraine, Laboratory publishing house) when the Ukrainian people boldly and selflessly defended, and still continue to defend their country from Russian unprovoked aggression. This book is autobiographical and does not focus only on the reflections of J. Comey during his tenure as a director of the FBI. The author begins the story from childhood and analyzes some events and circumstances which influenced his willingness to fight «hooligans». The first half of the book is devoted to his career in the federal prosecutor's office: assistant district attorney, district attorney, and eventually U.S. Deputy Attorney General. J. Comey describes numerous scandals involving White House officials and the Justice Department's struggle with the Bush administration over the legality of covert surveillance and interrogation programs. The second half of the book is dedicated to J. Comey's tenure as director of the FBI. Obviously, the main readers' attention is focused on the events related to the U.S. presidential election in 2016. J. Comey's decision to reopen the case against H. Clinton 11 days before the election and not to make public information about the investigation into Russian interference in the election is debatable and subject to speculation. J. Comey devoted most of this chapter to explaining his motivation for the first and second decisions. J. Comey’s work with the Trump administration, which is shrouded in rumors and scandals well enough described by the author. The former FBI director spares no words to express his own attitude toward the personal qualities and actions of the new president